Water clarity measures as indicators of recreational benefits provided by U.S. lakes: Swimming and aesthetics. (October 2018) - Angradi, Ted R.; Ringold, Paul L.; Hall, Kim
Highlights: Lakes provide recreations benefits that increase human well-being. Quality of recreational benefits is related to water clarity. Relationship to benefits is stronger for Secchi depth than for chlorophyll- a. Threshold values in benefit quality (exceptional, high, low, marginal) can be derived for water quality measures. Expectations of water clarity for a given level of benefits was lower in plains ecoregions than mountain ecoregions. Abstract: Lakes provide recreational benefits related to water quality. Using data from the 2007 and 2012 United States National Lake Assessments ( N  = 2067 lake visits), we developed indicators for three benefits: swimming, general recreational value, and aesthetic appeal. For two combined ecoregions ("Mountains" and "Plains") we related objective measures of water clarity, including Secchi depth, turbidity, and water-column chlorophyll- a concentration to subjective visual assessments of recreational benefit quality. There were significant associations between water clarity measures and visual assessments from which we derived water-clarity based thresholds between benefit quality classes (exceptional, high, low, marginal) for each benefit type. More variation in Secchi depth and turbidity was explained by benefit quality than was variation in chlorophyll- a . Threshold values were different between combined ecoregions. Compared to lakes in the Mountains ecoregion, recreational users of Plains lakes have lower expectations for water clarity. Thresholds were generally in accord with water clarity thresholds and guidance derived from published regional studies. Including indicators of the quality of benefits humans receive from lakes in assessments of lake conditions can increase public participation in decision-making and reveal changes in benefit quality over time.